The morphology and development of Kalahroud Cave, Iran - Shirin Bahadorinia; Sayed Hassen Hejazi; Alireza Nadimi; Derek C. Ford; Karine Wainer (International Journal of Speleology, 2016)
Kalahroud Cave is located in central Iran, ~50 km north of Isfahan. The landscape is a typical mountain desert morphology of cuestas dissected by ravines and gorges created during rare surface run-off events; crest lines are ~2800 m asl and lowlands at ~2100 m asl. Kalahroud Cave (4500 m of mapped passages, ~60 m deep) is entered through breakdown in the eastern wall of a gorge. The host rock is a Cretaceous limestone and mudstone formation 60 m in thickness, underlain by sandstones and conglomerates and overlain by weakly permeable calcareous marl strata, all dipping 15-20o. Below the entrance breakdown, two corrosion notch chambers give access to a rectilinear, quasi-horizontal maze of joint-guided passages extending ~500 m eastwards. Rock solution morphology created by slowly flowing phreatic waters predominates (solution pockets, partitions, paragenetic forms, etc). Seven shafts are known that discharged water into the maze and chambers from inaccessible passages below. From XRD analysis, the paragenetic sediments derive from the mudstone interbeds. There are small displays of frostwork, helictites and thin flowstones typical of vadose speleothem deposition in arid caves. Below the level of the corrosion notch, more complex sub-aqueous and shelfstone calcites are overlain by accumulations of calcite rafts up to 70 cm in depth. Raft deposition continues today. It is proposed that the cave is of hypogene origin, serving to discharge interformational groundwaters into the gorge, and becoming de-watered as the latter was deepened. The corrosion notches are due to cessation of deepening. From U series dating, the modern phase of raft deposition began about 10,000 years ago. The sequence and ages of older events will be investigated in future work.